An integrated control strategy for the composite braking system of an electric vehicle with independently driven axles. Issue 8 (2nd August 2016) - Sun, Fengchun; Liu, Wei; He, Hongwen; Guo, Hongqiang
ABSTRACT: For an electric vehicle with independently driven axles, an integrated braking control strategy was proposed to coordinate the regenerative braking and the hydraulic braking. The integrated strategy includes three modes, namely the hybrid composite mode, the parallel composite mode and the pure hydraulic mode. For the hybrid composite mode and the parallel composite mode, the coefficients of distributing the braking force between the hydraulic braking and the two motors' regenerative braking were optimised offline, and the response surfaces related to the driving state parameters were established. Meanwhile, the six-sigma method was applied to deal with the uncertainty problems for reliability. Additionally, the pure hydraulic mode is activated to ensure the braking safety and stability when the predictive failure of the response surfaces occurs. Experimental results under given braking conditions showed that the braking requirements could be well met with high braking stability and energy regeneration rate, and the reliability of the braking strategy was guaranteed on general braking conditions.